Longitudinal Trajectories and Correlates of Post-Caregiving Depressive Symptoms in Former Caregivers of Persons With Alzheimer's Disease or a Related Dementia. (June 2022) - Magan, Kristin Corey; Hirschman, Karen B.; Starr, Lauren T.; Meghani, Salimah H.
Background: Despite the end of caregiving responsibilities, caregivers' depressive symptoms continue following the death of the care recipient with Alzheimer's disease or a related dementia (ADRD). However, long-term patterns of depressive symptoms among ADRD caregivers following the care recipient's death remain poorly understood. Purpose: To explore longitudinal trajectories and correlates of depressive symptoms in former caregivers of persons with ADRD following the care recipient's death. Methods: Using the modification of Cooper's framework presented by Whittemore and Knafl, an integrative review was conducted in 4 stages: problem identification, literature search, data evaluation, and data analysis. The literature search was performed using CINAHL, PubMed, and PsycINFO databases. Articles were included if they were published in English between January 1994 and March 2021, reported in peer-reviewed sources, and described findings of original research related to factors, correlates, or longitudinal patterns of depressive symptoms in former family caregivers following the death of the care recipient with ADRD. Results: Longitudinal trajectories of depressive symptoms were categorized into 3 overarching themes: (1) gradual reduction of depressive symptoms during the first year post-caregiving; (2) failure of depressive symptoms to fully resolve after the first year post-caregiving; and (3) individualized depressive symptom trajectories. Correlates of post-caregiving depressive symptoms were categorized into 3 themes: (1) caregiver personal characteristics; (2) extrinsic factors; and (3) coping resources. Conclusion: These findings indicated that screening for depression and psychosocial support are high priorities during the first year post-caregiving to facilitate early identification of at-risk caregivers and improve mental health outcomes in this population.